Arsenic contamination at the Bagnoli Bay seabed (South Italy) via particle tracking numerical modeling: Pollution patterns from stationary climatic forcings. (September 2022) - Buccino, Mariano; Daliri, Mohammad; Buttarazzi, MS. Norma; Del Giudice, Giuseppe; Calabrese, Mario; Somma, Renato
Abstract: Almost 140 years of industrial exploitation have severely degraded the environment of Bagnoli Coroglio (BC), the westernmost neighborhood of the city of Naples (Italy). In this peculiar area, however, geogenic processes overlap with the impact of human activities, making it difficult to distinguish between anthropogenic and geogenic pollution sources. This is particularly true for Arsenic, the concentration of which in the marine sediments largely exceeds the tolerable level for human health and the background value for local pyroclastics. After several studies have used traditional tools based on multivariate statistics, this article attempts at tackling the problem via numerical modeling, which provides a deeper insight into the physics that governs the pollution process. Therefore, we use a particle tracking model to assess whether arsenic levels in the seabed can be affected by the influx of thermal water from an artificial channel outfalling at the westernmost part of the coast The climatic forcings that drive the marine circulation are simplified to basic "scenarios", in which wind and waves are stationary in strength and direction. Since the simulation time is much less than the contamination timescale, the comparison between numerical results and measurements is essentially qualitative and concerns the shape of contamination contours. It was found the primary forcing that enables seabed pollution is the tidal circulation, which, moreover, acts continuously in time. Quantitative arguments based on regression analysis suggest the discharge of thermal water explains almost a quarter of the observed pollution, which is consistent with previous research based on multivariate statistics. Graphical abstract: Image 1 Highlights: We used a particle tracking numerical model to assess the impact of an artificial drain on arsenic contamination of marine sediments in Bagnoli bay (South Italy). We measured the flow rate of the drain between February and June 2021. We used climate forcings including tides, wind and waves. We compared numerical contamination patterns to measurements carried out within the research project ABBaCo. We found out tidal circulation is the leading driver of the contamination process.